Clean Coal Energy: The Perspective of Environmental Law on Steam Power Plants in Indonesia - Yulida, Devi; Novindra, Dedy (Mahadi: Indonesia Journal of Law, 2025)
The use of coal as a primary energy source in Indonesia has made a significant contribution to meeting the nation's electricity demand. However, coal utilization also leads to serious environmental impacts, such as greenhouse gas emissions and air pollution. Clean Coal Energy has emerged as a solution that is expected to reduce environmental impacts through the application of technologies, such as carbon capture and storage (CCS), which aim to capture and store CO2 produced during coal combustion. Nevertheless, the implementation of this technology must align with environmental regulations, both those outlined in international legal instruments and those applicable in Indonesia. This study aims to examine the concept and implementation of clean coal energy in Steam Power Plants (PLTU) in Indonesia, as well as to review environmental law perspectives related to this matter. The writing employs a juridical-normative method, with a legislative approach and a conceptual approach. The research is conducted by qualitatively examining secondary data, which includes primary legal materials and secondary legal materials. These data are then presented in a narrative text. The research findings indicate that although clean coal energy can be a temporary alternative in the energy transition, its implementation still faces significant challenges. These challenges include issues related to regulations, high investment costs, and the effectiveness of the technology in reducing environmental impacts. Therefore, more integrated policies between environmental protection and national energy policies are needed, so that this technology not only reduces carbon emissions but also supports long-term environmental sustainability.